Croatia: Agricultural Land as Resource of Interest – Adjustment of Acquisition of Agricultural Land by Foreigners to EU Market Freedoms - Josipović, Tatjana (Acquisition of Agricultural Lands, 2022)
This article presents a special property regime for agricultural land in the Republic of Croatia, by which agricultural land, as a resource of interest to the Republic of Croatia, is granted special protection. The author analyzes Agricultural Land Act provisions providing statutory restrictions on the ownership of agricultural land and assesses their alignment with the Constitution of the Republic of Croatia regarding the constitutional guarantee of ownership and freedom of entrepreneurship. Special attention is given to the impact of EU law on the specific property regime of agricultural land. Some aspects of the property regime for agricultural land had to be aligned with EU market freedoms. During the accession negotiations, Croatia was bound to harmonize its national rules on foreigners’ property rights with EU market freedoms. Within these processes, the restrictive rules on the prohibition of acquisition of ownership of immovables have been changed in favor of foreigners. The author also analyzes the effects of the changes and their impact on the development of the agricultural land market. She emphasizes that upon the expiry of the transitional period (June 30, 2023), when the application of the discriminatory prohibition of acquisition of agricultural land on nationals and legal persons from other member states will no longer be possible, the development of the market of agricultural land will have to be incited by different, nondiscriminatory, and nonrestrictive measures. Keywords: agricultural land, private agricultural land, state-owned agricultural land, transitional period,specific property regime, resources of interest of the Republic of Croatia, particular statutory restrictionson ownership